LUMBERJANES : THE GOOD EGG / BOOK THREE - Tamaki, Mariko; Allen, Brooklyn (New York : Amulet Books, 2018)
"When Ripley comes across an abandoned egg, she's determined to take care of it until the parent comes back. Unfortunately, her plan is quickly foiled by egg poachers, who steal the egg for their own collection"--
"Based on the Lumberjanes comics created by Shannon Watters, Grace Ellis, Noelle Stevenson & Brooklyn Allen
Keywords: Girls -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Action and adventure fiction